IMPLEMENTASI NILAI NILAI HALAL DALAM OPERASIONAL AYAM PENYET MADINAH - Zainarti Zainarti; Zulfahri Salim; Wahyudin Wahyudin; Asnawi Asnawi (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to analyze the implementation of halal values in the operational activities of Ayam Penyet Madinah, located at Jalan Tempuling No. 636, Siderejo Hilir District, Medan Tembung Regency. Using a qualitative method through observation and in-depth interviews with the business owner, Mr. Jhony Perdana, this research examines how halal principles are applied from raw material selection, production processes, human resource management, to customer service. The results indicate that Ayam Penyet Madinah consistently implements halal values across all operational aspects, although the official halal certification is still in process. This halal implementation contributes to increased consumer trust and loyalty as well as business sustainability. However, challenges such as limited access to certified halal raw materials and the need for enhanced employee understanding must be addressed through management innovation and continuous training. This study provides practical and theoretical contributions to the development of quality and competitive halal culinary businesses.